The Moderating Effect of Artificial Intelligence and ICT Adoption on Tax Evasion - Sari Dewi; Gary; Hanini Ilyana Che Hashim; Kennardi Tanujaya (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
The primary purpose is to provide a relationship between corruption and tax evasion and explain the use of AI and electronic devices as a means of connection based on today's technological advances. The method of data collection type of questionnaire used is the Likert scale. Data analysis used SEM-PLS because it has a high level of flexibility. The main findings are that tax evasion cases always occur in any country and vary in nominality. Tax regulations and corruption cases have an impact on reducing tax compliance. Theory and practical implications Through this research, the insights of parties regarding tax evasion will be broader for all parties who report taxes to increase the value of tax compliance. In addition, the government will understand the relationship of problems in the country. The level of tax evasion has results similar to those of most other studies that have a strict relationship with a country's tax regulations.